A Chinese Medicine Formula (Bushen Huoxue Tongluo) for the Treatment of Chronic Subjective Tinnitus: A Study Protocol for a Pilot, Assessor-Blinded, Randomized Clinical Trial - Zhang, Hong Wei; Yeung, Kammy N. K.; Tong, Michael C. F.; Lin, Zhi-Xiu; Chang, Waitsz W. T.; Ng, Iris H-Y.; Sum, Chi Him; Leung, Ka Chun; Chan, Kam Leung; Ngan, Kit; Tong, Tie Jun (Frontiers in Pharmacology, 2022)
Background: Tinnitus is a common problem worldwide. There is still no effective method to cure it. Traditional Chinese medicine (TCM) may be a potentially effective treatment approach for tinnitus. However, there is still no clinical trial with scientifically rigorous methodology to evaluate the treatment effect of TCM for tinnitus. Therefore, we propose a pilot study to inform the feasibility of a future full-scale RCT to establish the efficacy of TCM formula for tinnitus. Objectives: The aim of this study is to determine the feasibility of a full-scale RCT and explore whether a TCM formula (BHT) has an additional effect on improving tinnitus when compared to informative counseling alone. Design: An assessor-blinded, randomized, controlled clinical trial is used. Participants: Twenty-four patients with chronic subjective tinnitus will be enrolled. Interventions: The patients will be allocated randomly to receive a TCM formula (BHT, Bushen Huoxue Tongluo) and informative counseling or informative counseling alone. The oral BHT herbal granules will be taken twice per day continuously for 8 weeks. Main outcome measures: The primary outcomes include recruitment rate, intervention completion rate, and data completion rate to evaluate the feasibility. The secondary outcomes include Tinnitus Handicap Inventory, tinnitus functional index, tinnitus sensation level, self-rated visual analogue scale on tinnitus loudness and annoyance, Pittsburgh Sleep Quality Index, Hospital Anxiety and Depression Scale, and adverse event. The outcome measures will be collected at baseline, end of treatment, and 4-week follow-up. Discussion: This trial is currently ongoing and is recruiting patients. The expected study results will find some preliminary evidence about the clinical effectiveness of BHT on chronic tinnitus and will also determine if it is feasible to conduct a full-scale RCT of BHT and identify the necessary changes to the protocol if possible.